The Development of CT-S Learning Module on The Linear Motion Topic to Promote Computational Thinking - Isra Khasyyatillah; Kamisah Osman (Journal of Educational Sciences, 2019)
Computational Thinking (CT) is the main skill of the 21st century that is increasingly attracting more researchers to study how to implement CT in the learning and teaching process. Among the CT tools that can be used to develop CT is programming. Currently, availability and easily accessible programming tools have led researchers and educators to explore how to introduce CT in the context of learning and teaching in schools. Recognizing the importance of implementing CT in the classroom, this study aims to develop the CT-S (Computational Thinking and Scratch) module for the Linear Motion topic. The type of this study is research and development research to develop modules based on the ADDIE model to produce the CT-S module with validity and reliability. Data were analyzed using descriptive statistical analysis. The result showed that the CT-S module was valid. It is eligible to be used as the instructional material of Physics. This study implies that computational thinking skills can be integrated with other subjects besides computer science like physics. Therefore, teachers can design lessons that are relevant to the context and students' characteristics.